2017
DOI: 10.26740/jepk.v4n1.p76-91
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pendidikan Kewirausahaan, Pengalaman Berwirausaha, Dan Jenis Kelamin Terhadap Sikap Berwirausaha Pada Mahasiswa Fakultas Ekonomi Universitas Muhammadiyah Surabaya

Abstract: ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh pendidikan kewirausahaan, pengalaman berwirausaha, dan jenis kelamin terhadap sikap berwirausaha baik secara parsial maupun simultan. Populasi dalam penelitian ini adalah mahasiswa S1 angkatan 2012 dan 2013 Fakultas Ekonomi Universitas Muhammadiyah Surabaya terdiri dari 2 program studi yaitu akuntansi dan manajemen yang berjumlah 206 dengan sampel 103 orang. Adapun teknik pengumpulan data yang digunakan yaitu angket, wawancara, dan dokumentasi. Metode a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
3
4
1
5
Order By: Relevance
“…It can be concluded that each aspect of entrepreneur's human capital has a significant effect on marketing performance. This study also supports the empirical study of Wahyudiono (2016) which explains that education as a component of human capital influences entrepreneurial attitudes. This reflects that education, especially related to entrepreneurship accompanied by maximum knowledge about entrepreneurship will be able to influence entrepreneurial motivation.…”
Section: Direct Effects Of Human Capital Social Capital On Entrepreneurship Statistical Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…It can be concluded that each aspect of entrepreneur's human capital has a significant effect on marketing performance. This study also supports the empirical study of Wahyudiono (2016) which explains that education as a component of human capital influences entrepreneurial attitudes. This reflects that education, especially related to entrepreneurship accompanied by maximum knowledge about entrepreneurship will be able to influence entrepreneurial motivation.…”
Section: Direct Effects Of Human Capital Social Capital On Entrepreneurship Statistical Resultssupporting
confidence: 87%
“…High entrepreneurial aspirations are often a prerequisite for entrepreneurial growth (Madriz et al, 2018). This research study further supports research of Wahyudiono (2016) of the effect of education in the field of entrepreneurship on entrepreneurial attitudes. Education in the field of entrepreneurship if properly applied is able to encourage business, for example, the student entrepreneurship.…”
Section: Direct Effects Of Human Capital Social Capital On Entrepreneurship Statistical Resultssupporting
confidence: 82%
“…The curriculum of the Islamic Economics Faculty (FSEI) Study Program is not entirely based on entrepreneurial insight (N. Hidayah, 2016). Students cannot complete the assignments given regarding the entrepreneurship courses properly and correctly (Wahyudiono, 2017). However, the findings are not in line with the findings of Putri et al (2018).…”
Section: Curriculumcontrasting
confidence: 70%
“…Likewise, gender variable was also found different study results. On the one hand, previous researchers found that gender had a significant effect (Kolvereid & Isaksen, 2006;Malebana, 2015;Varghese & Hassan, 2012;Wahyudiono, 2016), while other researchers found the contrary (Setyawan, 2016;Yukongdi & Lopa, 2017). The results will expected to find the level of influence of those factors and which factors will the more dominant influence on student entrepreneurial intentions, so the lecture program can be conducted optimally.…”
Section: Abstrakmentioning
confidence: 92%
“…Traditionally, it had been assumed that men had a higher tendency for entrepreneurship than women (Turker & Selcuk, 2009). Morever, empirical evidence showed that gender correlated significantly with entrepreneurial intentions (Kolvereid & Isaksen, 2006;Malebana, 2015) and entrepreneurial attitudes both partially and simultaneously (Wahyudiono, 2016). Varghese & Hassan (2012) argued that women are more eager to build a business than men because women are more creative and have new ideas for good business.…”
Section: Abstrakmentioning
confidence: 99%